Optimal Design and Dynamic Control of an ISD Vehicle Suspension Based on an ADD Positive Real Network - Xiaofeng Yang; Long Yan; Yujie Shen; Yanling Liu; Changning Liu (IEEE Access, 2020)
As a two-terminal mass element, an inerter makes up for the lack of mass impedance in a traditional vehicle suspension system. A passive Inerter-Spring-Damper (ISD) suspension can significantly improve vibration isolation performance in a low frequency range, while the impact is not obvious in other frequency bands. To isolate a wider frequency of vibrations in a vehicle suspension system on the basis of an ISD suspension, this paper combines the concepts of using an Acceleration-Driven-Damping (ADD) approach, which can effectively suppress vibrations in medium and high frequency bands, and an ISD passive network, which is superior in low frequency bands. First, an ideal model optimization design method of an ISD vehicle suspension based on an ADD positive real network is proposed, and a second-order model is built. The parameters are optimized by means of the artificial fish swarm algorithm considering both positive real constraints and suspension performance constraints. Then, on the basis of the optimal ideal model, a radial basis function sliding mode controller is designed to control the ISD vehicle suspension system using a mechatronic inerter. Finally, simulations and experiments are carried out to verify the dynamic performance of the proposed ISD suspension. The results show that a controllable ISD suspension system based on an ADD positive real network can improve the suspension performance effectively and isolate a wide range of frequency vibrations. This research provides theoretical evidence and methodological guidance for further enriching the design and dynamic control of ISD suspension systems.